Enhanced Electrical Properties of Lead-Free Piezoelectric KNLN-BZ-BNT Ceramics With the Modification of Sm3+ Ions - Quan, Yi; Wang, Lingyan; Ren, Wei; Zhao, Jinyan; Zhuang, Jian; Zheng, Kun; Wang, Zhe; Karaki, Tomoaki; Jiang, Zhishui; Wen, Li (Frontiers in Materials, 2021)
Environment-friendly lead-free piezoelectric ceramics with great properties and high thermal stability are desired in the industry. In this work, the Sm3+-modified lead-free 0.915(K0.45Na0.5Li0.05)NbO3-0.075BaZrO3-0.01(Bi0.5Na0.5)TiO3 (KNLN-BZ-BNT) ceramics were prepared. The piezoelectric properties are improved with the introduction of Sm3+ and the optimal properties (d33=325 pC/N and d33*=384 pm/V) were achieved in the ceramic modified withwith0.3 mol.% Sm3+ ions. Meanwhile, this sample shows a good thermal stability which the values of d33* decreased less than 20% during the temperature raised from 30 oC to 180 oC. These results show the Sm3+ modified KNLN-BZ-BNT ceramics are good for further applications even under high temperature.